A Checklist of Navicula (Class Bacillariophyceae) of the Philippines - Martinez-Goss, Milagrosa (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 1 (2001), 2007)
A unified acocunt of all known diatoms in the genus Novicula, class Bacillariophyceae, of the Philippines from 1886 to 1987 is presented. A total of 226 taxa are listed. Included herewith are the references that originally described or cited the taxon and the ecological/habitat records for each taxon. As much as possible, a list of exsciccata materials is given together with their repository places.
Keywords: Navicula; Bacillariophyceae; Philippines; diatoms